Ecological Rehabilitation And Public Participation: General Considerations And Empirical Evidence From A Creek Rehabilitation Scheme Near Cologne, Germany - Braun, Boris; Shoeb, AZM (Journal of Life and Earth Science, 2012)
Ecological rehabilitation of rivers and streams has become a common practice in environmental planning and water management throughout Europe. With regard to rehabilitation projects public participation and bottom-up planning processes are favoured by state and local regulations alike. However, there are mixed experiences about public support of rehabilitation schemes. Whereas people support environmental improvements on a general level, acceptance is dwindling when conflicts of use arise or access to certain areas is going to be restricted. This study focuses on the assessment of public attitudes to rehabilitation and on improving the understanding of people’s preferences. The results of a representative questionnaire survey conducted in three villages along a rehabilitated creek in a densely populated suburban area near Cologne show that local support for rehabilitation is generally high. More than two thirds of all residents support the rehabilitation scheme even when considering the costs involved. This support, however, varies between different age groups, with young adults being more sceptical than older people. The reasons for the fact that the younger generation is less supportive with regard to rehabilitation schemes might be related to their lesser interest in local affairs in general as well as their involvement in leisure activities that cannot be performed in rehabilitation sites along a small creek. Moreover, the findings reveal that many people want to have unlimited access to rehabilitated areas for recreational activities. This reflects a trend towards the perception of nature as an individual consumer good and has to be considered by environmental managers – not only in Europe, but in other parts of the world as well. DOI: http://dx.doi.org/10.3329/jles.v6i0.9714 JLES 2011 6: 1-11